Developing a Community of Practice through Social Media to Facilitate Continuing Education of Medical Practitioners in Medical Research - Fauzia, Lathifa; Pramudita, Arcita Hanjani; Adhyatma, Galih Prakasa; Hartono, Andyta Nalaresi; Eryani, Ika Septiana; Isma , Talita Zata (eJournal Kedokteran Indonesia, 2024)
The emergence of COVID-19 has highlighted the significance of research in medical practice, particularly in low- and middle-income countries (LMICs) like Indonesia, where healthcare challenges are prominent. Therefore, this study introduces Arcandcoresearch, a non-institutional-based virtual Community of Practice (vCoP), aiming to address the research capacity gaps among medical practitioners. This study aimed to understand the possibility of using several social media platforms (Instagram, YouTube, and WhatsApp) in the vCoP for continuing medical education of general practitioners regarding medical research. Through Instagram, the project has gained substantial follower growth (1003 followers within 19 months); most were 25-34 years old (69%). Within six months, 124 medical practitioners participated in five sharing sessions via Zoom meetings. All participants who completed the feedback form were satisfied with the content delivery of the sessions. The recorded sharing sessions were then uploaded to the YouTube channel. It already had 150 subscribers until September 2023, with 397 viewers for the videos uploaded in 2022. We facilitated participants to discuss any concerns related to medical research in the WhatsApp group, which already had 24 participants. These preliminary results highlight the potential of Arcandcoresearch to impact medical research culture positively in LMICs. The next steps should be conducting thorough program evaluations and developing strategies for sustaining virtual engagement.